Hybrid liposomes showing enhanced accumulation in tumors as theranostic agents in the orthotopic graft model mouse of colorectal cancer - Okumura, Masaki (Drug Deliv, 2018)
Hybrid liposomes (HLs) can be prepared by simply sonicating a mixture of vesicular and micellar molecules in a buffer solution. This study aimed to elucidate the therapeutic effects and ability of HLs to detect (diagnosis) cancer in an orthotopic graft mouse model of colorectal cancer with HCT116 cells for the use of HLs as theranostic agents. In the absence of a chemotherapeutic drug, HLs exhibited therapeutic effects by inhibiting the growth of HCT116 colorectal cancer cells in vitro, possibly through an increase in apoptosis. Intravenously administered HLs also caused a remarkable reduction in the relative cecum weight in an orthotopic graft mouse model of colorectal cancer. A decrease in tumor size in the cecal sections was confirmed by histological analysis using HE staining. TUNEL staining indicated an induction of apoptosis in HCT116 cells in the orthotopic graft mouse model of colorectal cancer. For the detection (diagnosis) of colorectal cancer by HLs, the accumulation of HLs encapsulating a fluorescent probe (ICG) was observed in HCT116 cells in the in vivo colorectal cancer model following intravenous administration. These data indicate that HLs can accumulate in tumor cells in the cecum of the orthotopic graft mouse model of colorectal cancer for a prolonged period of time, and inhibit the growth of HCT116 cells.